Consciousness and Change : Symbolic Anthropology in Evolutionary Perspective - Peacock, James L. (Book collections on Project MUSE., 2021)
Symbols and symbolism are, and always have been, an integral part of myth, belief, ideology, ritual, art, and fantasy. These basic areas of human activity are traditionally investigated under a very wide range of headings; but this book ignores the boundaries of such diverse disciplines as political science, religious sociology, psychology, and literature. Originally published in 1975, Consciousness and Change draws upon all these sources, and more; the result is both an introduction to and a perspective on the developing (though at the time by no means clearly defined) field of symbolic anthropology. The book opens with an analysis of symbols, discussing some of their essential qualities. The author then proceeds to examine the Durkheimian and Weberian schools of thought, as reflected in the works of anthropologists ranging from Levi-Strauss to Clifford Geertz; next, he considers the development of Protean symbolism, using material material derived from his own field experience in the U.S. South and elsewhere. He concludes with a typology relating different types of symbols to different periods of history, from the primitivism of the Australian aborigine to the quasi-primitivism of the modern commune-dweller. While it is not intended as a comprehensive textbook, Consciousness and Change provides student and lay reader alike with an introductory overview of the anthropology of symbols.